2017
DOI: 10.1007/978-3-319-69341-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Cybersecurity Risk Taxonomy

Abstract: In cybersecurity, the identification of risks is a fundamental part because this activity is not unique to cybersecurity and it is hard to know what the risks in this area are. This study aims to identify if there are some risk taxonomies in cybersecurity. For this, a systematic review of the studies published from 1990 to 2017 was carried out. We found 132 papers and some of them mention some risk taxonomies within the scope of IT (information technologies) cybersecurity, although only five primary elements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…There is an ongoing exploration on the various ways to classify and taxonomise cyber risk loss events, see discussions in Shevchenko et al (2023), Rea-Guaman et al (2017) and Elnagdy et al (2016). In this study the focus has been on the U.S. cyber risk experience as it is generally the environment where the largest commercial cyber loss data collection effort has been instigated, both in terms of breadth of industry and loss type as well as in terms of duration of collection and reporting.…”
Section: Data Description and Attributesmentioning
confidence: 99%
“…There is an ongoing exploration on the various ways to classify and taxonomise cyber risk loss events, see discussions in Shevchenko et al (2023), Rea-Guaman et al (2017) and Elnagdy et al (2016). In this study the focus has been on the U.S. cyber risk experience as it is generally the environment where the largest commercial cyber loss data collection effort has been instigated, both in terms of breadth of industry and loss type as well as in terms of duration of collection and reporting.…”
Section: Data Description and Attributesmentioning
confidence: 99%
“…There is an ongoing exploration on the various ways to classify and taxonomize cyber risk loss events, see discussions in [7,23] and [24]. In this study the focus has been on the US cyber risk experience as it is generally the environment where the largest commercial cyber loss data collection effort has been instigated, both in terms of breadth of industry and loss type as well as in terms of duration of collection and reporting.…”
Section: Data Description and Attributesmentioning
confidence: 99%
“…Considering that cybersecurity risks are the starting point of all cybersecurity maturity models, a systematic review (SR) regarding cybersecurity risk taxonomies was carried out [24]. In this SR, it was found that some articles [12][13][14] identify international standards as references, such as the standards of the National Institute of Standards and Technology (NIST) [15].…”
Section: Contextmentioning
confidence: 99%
“…From the snowball technique [25] applied to the articles obtained by the systematic review [24], the main elements of the conceptual model of cybersecurity risk management and their relationships have been determined. This information has served as the basis for the design of the proposed conceptual model.…”
Section: Contextmentioning
confidence: 99%